Semigroups of bounded operators and second-order elliptic and parabolic partial differential equations - Lorenzi, Luca; Rhandi, Abdelaziz (Boca Raton : Chapman & Hall/CRC, 2020)
Semigroups of Bounded Operators and Second-Order Elliptic and Parabolic Partial Differential Equations aims to propose a unified approach to elliptic and parabolic equations with bounded and smooth coefficients. The book will highlight the connections between these equations and the theory of semigroups of operators, while demonstrating how the theory of semigroups represents a powerful tool to analyze general parabolic equations. Features Useful for students and researchers as an introduction to the field of partial differential equations of elliptic and parabolic types Introduces the reader to the theory of operator semigroups as a tool for the analysis of partial differential equations
OCLC-licensed vendor bibliographic record.
Keywords: Differential equations, Elliptic; Differential equations, Parabolic; Semigroups of operators; Operator theory; MATHEMATICS / Differential Equations; MATHEMATICS / Geometry / Algebraic